Learning‐induced modulations of the stimulus‐preceding negativity. (30th June 2013) - Morís, Joaquín; Luque, David; Rodríguez‐Fornells, Antoni
Abstract The neural basis of feedback expectation, which is crucial in learning theory, has only been minimally studied. Stimulus‐preceding negativity (SPN), an ERP component that appears prior to the presentation of feedback, has been proposed as being related to feedback expectation. The present study showed, for the first time, amplitude modulations of the SPN component during learning acquisition in a trial‐by‐trial associative learning task. The results indicate that SPN could be a plausible electrophysiological index of the cognitive processes engaged while expecting the appearance of relevant feedback during reinforcement learning.